For every season ebook Book three in the amish vines and orchards series. - Woodsmall, Cindy (Amish Vines and Orchards, 2013)
Working hard to develop a new Amish community outside of Unity, Maine, Rhoda Byler is fully committed to rehabilitating an orchard with business partner Samuel King. But an impulsive decision has created an unexpected strain in her relationship with her beau, Samuel’s brother, Jacob, threatening plans for the orchard. Amidst mounting tension in matters of the heart and business, Rhoda finds that this fledging settlement feels like the home she has always longed for, and she begins to embrace the God-given, heightened intuition that has always felt like a burden to her. She longs for Jacob to fully be free of his past, so they can work towards the future together.   But as Rhoda uses her gift to unpack an old secret with her Englisch neighbors, it is not her beau but an unlikely ally that cheers her on. With the orchard on shaky ground and Jacob’s plans in question, Rhoda is determined to see things through to harvest. But can she trust her insight to direct her path in matters of the heart?